A fluid-kinetic approach for 3D plasma edge transport in He plasma. (21st March 2017) - Rack, M.; Reiter, D.; Hasenbeck, F.; Feng, Y.; Börner, P.; Weger, A.-C.; Cosfeld, J.
Abstract: The fluid edge plasma Monte-Carlo code in three dimensions (EMC3) coupled to the kinetic (neutral particle) transport code EIRENE has demonstrated good performance in describing and even predicting the experimental trends of a wide range of stellarator and tokamak edge plasma configurations, under a certain range of relevant limiter and divertor scenarios. One major limitation so far, however, has been the restriction of EMC3 to hydrogen isotopes, although in the initial operation phase of the newly built, optimised stellarator Wendelstein 7-X, (and probably also in ITER during its initial low activation phase) helium plasmas are used. An approach is presented on how to extend EMC3 and expand the use of EIRENE features in plasma edge simulations for helium edge plasmas. The approach is based on modelling He ++ as a fluid, calculated by the plasma fluid code EMC3, and treating helium atoms and He + ions as particles, calculated by the kinetic transport code EIRENE. The applicability, current limitations and future directions of this hybrid approach will be discussed. The first simulation results for Wendelstein 7-X helium edge plasma conditions demonstrate the feasibility of the present computational model.